Capacity Building for Village Officials in Information System Governance in Ngaban Village - Dinda Aulia Putri; Ilmi Usrotin Choiriyah (Kolaborasi : Jurnal Administrasi Publik, 2026)
Digital information governance has become a strategic tool for achieving transparent, accountable, and responsive village governance. However, most research on village information systems still focuses narrowly on the development of technical platforms, while the dimensions of organizational capacity and human resources—which determine the sustainability of implementation, particularly at the level of village officials—have not been extensively studied. This study addresses this gap by analyzing how capacity building shapes information system governance in Ngaban Village, Tanggulangin Subdistrict, Sidoarjo Regency, using Grindle’s (1997) framework, which encompasses human resource development, organizational strengthening, and institutional reform. The study employed a descriptive qualitative method, involving three key informants selected through purposive sampling (the Village Secretary, the Head of Government Affairs, and the Head of Planning) due to their direct knowledge of village information management. Data were collected through in-depth interviews, observations, and documentation from October to December 2025. Data were analyzed using the Miles and Huberman interactive model and validated through source and method triangulation. The findings indicate that although village officials possess adequate human resources and a well-defined organizational structure, capacity-building efforts remain focused on general administrative training; no personnel have been specifically assigned to manage the digital information system; and the village website remains underutilized as a public information channel. These findings expand Grindle’s framework by demonstrating that structural readiness alone does not automatically result in functional digital governance without the assignment of specific roles. This study offers practical implications for village governments in strengthening digital information governance and suggests that future policies prioritize role-specific digital training and the placement of dedicated information management personnel at the village level